Motivasi internal perawat terhadap pelaksanaan dokumentasi edukasi terintegrasi di ruang rawat inap - Dewi Kusumaningsih; Agustina Sianturi (Holistik Jurnal Kesehatan, 2020)
The health educational intervention and inpatient documentation execution  and an internal motivation among nursesBackground: Documentation of the health educational to inpatient is a nursing that evidence record the service of nursing care given to the patients that is useful for patients, nurses, health staffs and hospital. Most of the hospital in Bandar Lampung in the pre-survey, there were of 30% medical records was incomplete filled such as time and date when giving nursing care and signed by nurses, and mostly regarding in health educational documentations.Purpose: To identify the nursing documentation perfection (health education to the inpatient) and an internal motivation among nurses to executionMethod: A quantitative study with cross-sectional approach. The population and the sample were all inpatient nurses at Immanuel Hospital of Bandar Lampung in 2019 of 75 respondent and 75 medical records. The instrument as a questionnaire to explore nurses' internal motivation. Medical record to observe nursing note.Results: Finding of 52.0% respondent has made an incomplete nursing documentation and 46.7% respondents exhibited a poor in internal motivation. The p value was 0.004; and OR 4.643.Conclusion: There was a correlation between nurses' internal motivation and the completeness of health educational documentation. The nurse supervisor should regularly do evaluation the completeness of health educational documentation and hospital management to encourage nurses's internal motivation.Keywords: The health educational; Intervention; Inpatient documentation; Execution; An internal motivation; NursesPendahuluan: Dokumentasi edukasi keperawatan merupakan bukti tertulis perawat atas pelayanan asuhan keperawatan yang diberikan kepada pasien yang berguna untuk kepentingan pasien, perawat, tim kesehatan lain dan rumah sakit. Saat pre survey didapatkan 30% dokumentasi edukasi pasien tidak terisi waktu dan tanggal pelaksanaan, 10% dokumentasi edukasi dalam pasien tidak terisi bagaimana kebutuhan edukasi, selain itu sebanyak 10%  pasien pindahan dalam lembar edukasi tidak terisi tujuan pemberi edukasi di dalam form tersebut.Tujuan: Diketahui hubungan motivasi internal perawat terhadap kelengkapan dokumentasi edukasi di ruang bangsal dewasa Rumah Sakit Imanuel Bandar Lampung tahun 2019.Metode: Jenis penelitian kuantitatif, desain penelitian analitik pendekatan cross sectional. Populasi dan sampelnya  seluruh perawat pelaksana di ruang bangsal  Rumah Sakit Imanuel Bandar Lampung, sejumlah 75 responden dan 75 catatan keperawatan dalam medical record. Instrumen berupa angket untuk mengetahui motivasi internal perawatHasil: Diketahui dari 75 responden sebanyak (52,0% responden melakukan pendokumentasian tidak lengkap. Diketahui dari 75 responden sebanyak 46,7% responden yang mempunyai motivasi internal kategori rendah. Didapatkan hasil p-value=0,004; OR 4,643.Simpulan: Ada hubungan motivasi perawat terhadap kelengkapan dokumentasi edukasi di ruang bangsal dewasa Rumah Sakit Imanuel Bandar Lampung tahun 2019. Saran diharapkan kepala ruangan dapat mengevaluasi secara rutin tentang kelengkapan pengisian dokumentasi edukasi